Costus Afer Ker Gawl Leaves Against Gentamicin-induced Nephrotoxicity in Rats (Iranian Journal of Kidney Diseases, 2014)
Introduction. The nephroprotective effect of the aqueous extract of Costus afer leaves was evaluated in male albino Wistar rats with gentamicin-induced kidney injury. Materials and Methods. In a 2-phase study, 30 weight-matched male Albino Wistar rats were divided into 6 groups of 5 animals to receive gentamicin, 90 mg/kg/d (except for the control group) for 7 days in the first phase to induce kidney injury. The second phase was treatment of rats with 375 mg/kg, 750 mg/kg, and 1125 mg/kg of aqueous extract of Costus afer leaves. One group received Silymarin only. Body weight, daily fluid and feed intakes, and serum levels of creatinine, urea, and electrolytes were monitored on a weekly basis, and renal histology was evaluated at the end of the study. Results. The aqueous extract of Costus afer significantly increased the feed intake and fluid intake in a dose dependent manner when compared with the gentamicin-treated group. Low and medium doses of the extract reversed the deleterious effect of gentamicin on the kidney. The extract also significantly decreased the absolute kidney weight and relative kidney weight when compared with the corresponding weights in the gentamicin-treated group. Costus afer significantly decreased serum sodium, blood urea, and serum creatinine levels and significantly increased serum potassium level in gentamicin-induced nephrotoxic rats. Conclusions. Aqueous extract of Costus afer leaves may attenuate gentamicin-induced nephrotoxicity  in rats.